ETHNOPHARMACOLOGICAL STUDIES OF TRIBULUS TERRESTRIS (LINN). IN RELATION TO ITS APHRODISIAC PROPERTIES - Mathur, Manish; Sundaramoorthy, S (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Synergism and antagonism impact of different plant metabolites present in crude fruit extract of Tribulus terrestris ‘the herbal Viagra’ have been studied. Variability in plant composition, biomass and metabolites concentration in different modules was significantly contributed by spatial factor. However the edhaphic parameters also changes with both spatial and temporal factors significantly. Fruit is the officinal part and the fruit production significantly related with soil nitrogen (P<0.01), whereas the soil nitrogen and pH also influenced the alkaloid content in fruit (P<0.05). The linear relation between fruit protein and fruit alkaloid (P<0.01) also observed and the relationship in between different soil parameters were established. Bioassay work confirmed its aphrodisiac properties, and site III is suggested for maximum biomass and high concentration of different metabolites.